2022
DOI: 10.18103/mra.v10i5.2810
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Covid-19-Associated Hypercoagulability with Functional Coagulation Assays and Extracellular Vesicles

Abstract: Most patients affected by the novel coronavirus SARS-CoV-2 — responsible for the Coronavirus disease, COVID-19 — remain asymptomatic or develop mild symptoms. Only a small percentage of cases develop a severe disease that may lead to a fatal outcome. Since the early reports published in the literature by Wuhan colleagues, we have learned that patients hospitalized for acute COVID-19 infection have different clinical and laboratory pictures of coagulopathy. In particular, a marked increase in blood clotting cap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 31 publications
(34 reference statements)
0
1
0
Order By: Relevance
“…Nevertheless, definitive consensus is lacking on whether COVID-19 hypercoagulability arises from a COVID-19-specific mechanism. Previous studies have found increased rates of coagulation parameters when comparing severe to mild COVID-19 disease but not when comparing COVID-19 to non-COVID-19 infection or when limited in sample size [27,28]. Comparing the rates of VTE between COVID-19 sepsis and non-COVID-19 sepsis is important because doing so would allow us to determine whether COVID-19 sepsis carries a unique risk of thrombosis compared to other forms of sepsis.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, definitive consensus is lacking on whether COVID-19 hypercoagulability arises from a COVID-19-specific mechanism. Previous studies have found increased rates of coagulation parameters when comparing severe to mild COVID-19 disease but not when comparing COVID-19 to non-COVID-19 infection or when limited in sample size [27,28]. Comparing the rates of VTE between COVID-19 sepsis and non-COVID-19 sepsis is important because doing so would allow us to determine whether COVID-19 sepsis carries a unique risk of thrombosis compared to other forms of sepsis.…”
Section: Introductionmentioning
confidence: 99%